Temporal Nature and Characteristics of Corporate Entrepreneurship : Growth and Renewal Implications - Gabryś, Bartłomiej J.; Bratnicki, Mariusz (Temporalna natura i charakterystyka przedsiębiorczości organizacyjnej : implikacje dla rozwoju i strategicznej odnowy, 2010)
This paper seeks to advance our understanding of time in the area of corporate entrepreneurship research. It suggest considering time as essential for understanding corporate entrepreneurship on the way to strategic renewal, where the problem is rooted in the reconciliation of time contradictions. Our conceptual model is supported empirically by the results from the survey carried out at the turn of 2007 and 2008 on the sample of 199 organizations. The results support the existence of five separate time contradictions: nature of time; structure of time; temporal frame of reference; experience of time; and time flow. Then we focus on the relations between time contradictions and corporate entrepreneurship. The authors argue that organizations which take our concept into management practice will achieve greater potential for growth and strategic renewal.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 28-38
Keywords: time; corporate entrepreneurship; growth